(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2024)
Cholecystectomy is a surgical intervention performed with the aim of removing the gallbladder, using different laparoscopic techniques, the intervention is performed with the application of a video camera and special materials without the need to open the patient’s abdomen. To carry out a bibliographic review of the scientific literature on post-surgical complications in cholecystectomy in Ecuador. A documentary study of literature review was carried out using a qualitative approach, with a descriptive design through the analysis and compilation of relevant information from scientific and academic sources. For the search for information, we worked with the databases Scopus, Pubmed, Web of Science and the library of the Catholic University of Cuenca. Post-surgical complications of cholecystectomy are related to sociodemographic factors, i.e. intrinsic factors such as age, sex, comorbidities and others, and extrinsic factors related to the surgical process. The most frequent post-surgical complications in laparoscopic cholecystectomy are: nausea, vomiting, wound infection, jaundice preceded by pancreatitis, choledocholithiasis, while in open cholecystectomy they are: nausea and vomiting, lower abdominal pain, gastritis, jaundice, diarrhoea, irritable bowel syndrome.